Bird flu in Nepal - Thapa, Kajol; Mishra, Ved Prakash; Twanabasu, Suraj; Kusma, Susan (International Journal of Research in Medical Sciences, 2020)
Avian flu also known as bird flu is caused by deadly virus H5N1 which initially was found in birds and wild animals, however, later it was found in human beings causing severe respiratory related problems. This review article was performed to understand the epidemiology of outbreaks of H5N1 in different districts of Nepal. First outbreak of strain H5N1 was reported in 2009. Consequently, highest number of outbreaks i.e. 201 was noted in the year 2013. Till date only one human case was identified by NPHL which was later confirmed by genetic laboratory in Japan in collaborating with WHO.